2014
DOI: 10.3390/w6072084
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Numerical Modeling of Flows through Vegetation Using a Mixing-Length Turbulence Model

Abstract: This work focuses on the effects of vegetation on a fluid flow pattern. In this numerical research, we verify the applicability of a simpler turbulence model than the commonly used k-ε model to predict the mean flow through vegetation. The novel characteristic of this turbulence model is that the horizontal mixing-length is explicitly calculated and coupled with a multi-layer approach for the vertical mixing-length, within a general three-dimensional eddy-viscosity formulation. This mixing-length turbulence mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…It is visible that the velocity has maximum value above the vegetation zone. Hector Barrios-Pina et al [29], in their numerical investigation through double-layered vegetation, also found that the flow velocity rises above the vegetated region.…”
Section: Mean Flow Characteristicsmentioning
confidence: 98%
“…It is visible that the velocity has maximum value above the vegetation zone. Hector Barrios-Pina et al [29], in their numerical investigation through double-layered vegetation, also found that the flow velocity rises above the vegetated region.…”
Section: Mean Flow Characteristicsmentioning
confidence: 98%
“…where Cz is the Chezy coefficient. This hydrodynamic model has been calibrated according to Casulli and Cheng [92], and has been tested in [67,68,70,93].…”
Section: Appendix a Hydrodynamicsmentioning
confidence: 99%
“…In this work, we performed an assessment of the flooding risk of Tamuín city, through a parallel self-made hydrodynamic model previously validated in diverse studies [66][67][68][69][70] and carefully calibrated with field measurements, with the idea of having full control of processes, methods and precision provided by owning the code. Streamflow of Tampaón River in wet and dry seasons was simulated according to historical records.…”
Section: Introductionmentioning
confidence: 99%
“…Barrios-Pina et al [23] verified the applicability of a simpler turbulence model than the commonly usedmodel to predict the mean flow through vegetation in shallow waters. However, despite the great number of versions of turbulence models based mainly on mixing length, -, and algebraic, none can be used universally for all kinds of problems, as the scale of the study domain and the computer equipment available must be considered.…”
Section: Introductionmentioning
confidence: 98%